PERBANDINGAN KARAKTERISTIK WINE LOKAL DAN WINE AUSTRALIA DENGAN BERBAHAN DASAR GRAPE VARIETY CHARDONNAY - Ni luh Suastuti; Ida Ayu Yulyarini Sugiantari (JURNAL GASTRONOMI INDONESIA, 2017)
Wine is an alcoholic drink made from fermented grapes or other fruits. Due to a natural chemical balance, grapes can ferment without added sugars, acids, enzymes, water or other nutrients. Although there is a common perception that it is almost impossible to grow wine and produce quality wines in the tropical climate of Asia, but the Hatten Wines company succeeded in establishing a successful wine industry. The products offered can be accepted by tourists. Hatten Wines also produces wine using imported Australian grape, one of which is wine with the brand of Two Island. This type of wine uses the type of Australian grape, and is made in Bali. Differences location of production will certainly create a different taste with other types of wine. The uniqueness of taste and aroma is what must be studied and developed more deeply to know the characteristics of the wine. By knowing more clearly about the characteristics of the local wine, and seeing from a variety of food in Indonesia, of course this local wine should also be developed to be combined with various types of food, or commonly referred to as “Food and Wine Pairing”. However, consumers’ interest in local wine is still relatively low either just to enjoy or to be combined with food, as consumers tend to prefer the type of wine produced outside because it is considered to have a better flavor.